Peran Transformasi Digital dalam Memperkuat Pengaruh Literasi Keuangan terhadap Kinerja UMKM - Ilham Fajar Eko Saputro; Nurlaelatul Maulidah; Hendra Lesmana; Ery Suryanti (Jurnal Sistem Informasi Akuntansi (JASIKA), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting Indonesia’s economy; however, the rapid development of digital technology and increasingly intense business competition require MSMEs to improve their financial management capabilities and technological adaptation. This study aims to empirically examine and analyze the effect of financial literacy on MSME performance with digital transformation as a moderating variable in culinary MSMEs in Tegal City. This research uses a quantitative approach with primary data obtained through questionnaires distributed to MSME actors. The population in this study consisted of culinary MSMEs in Tegal City, with a sample of 100 respondents selected using purposive sampling and determined through the Slovin formula. Data analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of SPSS version 25. The results of this study indicate that financial literacy has a positive and significant effect on MSME performance. In addition, digital transformation is proven to strengthen the relationship between financial literacy and MSME performance. These findings indicate that the ability to manage finances and utilize digital technology can improve business performance and competitiveness of MSMEs. Therefore, strengthening financial literacy and optimizing digital transformation are important strategies to support the sustainability and development of MSMEs in the digital era.